Gestational exposure to phthalates and gender-related play behaviors in 8-year-old children: an observational study. Issue 1 (December 2016) - Percy, Zana; Xu, Yingying; Sucharew, Heidi; Khoury, Jane; Calafat, Antonia; Braun, Joseph; Lanphear, Bruce; Chen, Aimin; Yolton, Kimberly
Abstract Background Phthalates, used in a variety of consumer products, are a group of chemicals that are ubiquitous in the environment, and their metabolites are detectable in most humans. Some phthalates have anti-androgenic properties; a prior study reported an association between gestational exposure to phthalates and reduced masculine behaviors in preschool boys. Methods Concentrations of 9 phthalate metabolites were measured in urine collected at 16 and 26 weeks' gestation from pregnant women enrolled in the HOME Study, a prospective pregnancy and birth cohort. Measures of gender-related play were collected at 8 years of age, including the Gender Identity Questionnaire (GIQ) completed by mothers, and the Playmate and Play Style Preferences Structured Interview (PPPSI) completed by children. We examined these measures as continuous variables using both bivariate and multivariable approaches with adjustment for covariates. Additional analyses included logistic regression of GIQ and PPPSI scores dichotomized by sex at the lower 25th percentile, indicating the least typical behavior. Results Mothers' phthalate metabolite concentrations during pregnancy were similar to the reported national average among US women. All children scored within a typical range on both measures of gender-related play behavior. No statistically significant associations were found between averaged maternal phthalate metabolite concentrations and continuous PPPSI scores or any GIQ scores. For the dichotomized PPPSI; higher maternal monoethyl phthalate (MEP) concentrations were associated with more typical play behaviors for females (OR  = 0.70, CI = 0.51–0.97). In contrast, higher maternal mono-isobutyl phthalate (MiBP) concentrations were associated with higher odds of membership in the least typical play behaviors group for males (OR  = 1.69, CI = 1.00–2.86). Conclusions In this sample of typically developing children, higher maternal urinary MEP concentrations during pregnancy were associated with more typical gender-related play behaviors in both males and females, and increased urinary MiBP concentrations were associated with less masculine gender-related play behaviors in males.